IMPLEMENTASI MODEL TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS V SDN MANGKURA IV - Muhajira; Nur faidah wiyatni; Nessa Mandani Herman; Nurfitri AR; Nur Irfani; Achmad Dzulikrami AP; Sulfasyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the implementation of the team games tournament learning model on the cognitive learning outcomes of fifth grade students of SDN Mangkura IV. This type of research is classroom action research with a pretest-posttest one group design. The population in this study was all fifth grade students of SDN Mangkura IV. The sample of this study was selected using a simple random sampling technique. The data collection technique used was an observation sheet and a multiple-choice test of 20 questions. The collected data were analyzed using descriptive statistics using SPSS. The results of the statistical test in cycle I showed the average post-test score in grade V in the subject of Social Sciences was 55.00. The minimum completion criteria obtained by students with a percentage of 26% in the completion criteria and 74% in the incomplete criteria. Then the results of the student learning test in cycle II obtained an average of 78.19%. The minimum completion criteria in cycle II obtained 81.5% in the complete category and 18.5% in the incomplete category. In cycle I to cycle II there was a significant increase. The conclusion of this study is that the application of the team games tournament model is effective in improving the cognitive learning outcomes of class V students at SDN Mangkura IV.